Metabolic Syndrome Is Associated with Oxidative Stress and Proinflammatory State - Margalida Monserrat-Mesquida; Magdalena Quetglas-Llabrés; Xavier Capó; Cristina Bouzas; David Mateos; Antoni Pons; Josep A. Tur; Antoni Sureda (Antioxidants, 2020)
Metabolic syndrome (MetS) is associated with increased risk of developing diabetes and cardiovascular diseases. MetS is also characterized by an increase of oxidative stress which contributes to impaired inflammation, vascular function, and atherosclerosis. The aim was to assess the oxidative stress and inflammatory markers in plasma and PBMCs in adults with or without MetS. Antioxidant and inflammatory parameters were measured in peripheral blood mononuclear cells (PBMCs) of 80 men and 80 women over 55 to 80-years-old residing in the Balearic Islands without previously documented cardiovascular disease. Circulating leukocytes, neutrophils, lymphocytes, basophils, and monocytes were higher in MetS subjects with respect to those without MetS. Plasma levels of malondialdehyde, tumor necrosis factor α (TNFα), and interleukin 6 (IL-6) levels were higher in MetS subjects in both genders, but the superoxide dismutase activity was lower. The myeloperoxidase plasma activity was higher in the MetS male subjects. Higher activities and protein levels of catalase and glutathione reductase in PBMCs were observed in MetS subjects in both genders. Obtained data show that MetS is associated with oxidative stress and a proinflammatory state and with high antioxidant defenses in PBMCs probably derived from a pre-activation state of immune cells.